The Impact of Globalization on Medical Students’ Identity Formation - Ardi Findyartini (Journal Kedokteran Indonesia, 2019)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> <!--StartFragment--> Globalization on medical education and health care allows medical students, medical trainees and medical doctors to study and work in different countries with various cultural contexts. Despite understanding that this is inevitable nowadays, it introduces certain challenges in medical education especially in preparing medical students and medical trainees who are prepared to socialize and interact with different culture. The process will be facilitated by solid professional identity formation as part of professional development of medical students and trainees who are becoming future medical doctors. This literature review aims to explore personal and professional identity formation and how medical education may support medical students to be culturally aware and competent in facing changing and dynamic world.